Peran Kepala Sekolah dalam Pembinaan Kompetensi Pedagogik Guru PAUD di PAUD X Bandung - Meilani Nurhayati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Principal coaching is the ability of the principal in moving the resources in school, aspects of the principal as coaching include 4 standards of competence, namely pedagogical competence, personality competence, professional competence, social competence. So this research aims to describe how the role of the principal in the development of pedagogical competence of teachers in PAUD X. The subjects of this study are the principal and teacher of PAUD X, using a qualitative approach, the type of sample used is purposive sampling, and using data collection techniques through interviews, observations, and documentation. The results of the principal are able to realize the confidence of several programs to further develop the level of pedagogical competence of teachers or educators by conducting training, assigning teachers to take training outside, encouraging teachers to further improve their knowledge and qualification levels. Abstrak. Pembinaan kepala sekolah merupakan kemampuan kepala sekolah dalam menggerakkan sumber daya yang ada disekolah, Aspek kepala sekolah sebagai pembinaan meliputi 4 standar kompetensi yaitu kompetensi pedagogik, kompetensi kepribadian, kompetensi professional, kompetensi sosial. Maka penelitian ini bertujuan untuk mendeskripsikan bagaimana peran kepala sekolah dalam pembinaan kompetensi pedagogik guru di PAUD X. Subjek penelitian ini adalah kepala sekolah dan guru PAUD X, dengan menggunakan pendekatan kualitatif, jenis sampel yang digunakan adalah purposive sampling, dan menggunakan Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Didapatkan hasil kepala sekolah mampu merealisasikan keyakinan beberapa program untuk lebih mengembangkan tingkat kompetensi pedagogik guru atau pendidik dengan Mengadakan pelatihan, Menugaskan guru untuk mengikuti pelatihan diluar, Mendorong guru untuk lebih meningkatkan pengetahuan dan tingkat kualifikasinya.